2018
DOI: 10.3349/ymj.2018.59.9.1072
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Hepatitis Viruses and Hepatitis B Genotypes of Female Marriage Immigrants in Korea

Abstract: PurposeThe Korean society has moved rapidly toward becoming a multicultural society. This study aimed to estimate the seroprevalence of hepatitis viruses and investigate hepatitis B virus (HBV) genotypic diversity in female marriage immigrants.Materials and MethodsScreening program was conducted at support centers for multicultural families in 21 administrative districts in Korea between July 2011 and January 2017. A total of 963 female marriage immigrants were included in this study. Blood samples were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Among the 35 included publications, the largest number were for Thailand (n = 20) [ 23 38 , 44 – 46 , 51 ] followed by Malaysia (n = 5) [ 20 , 41 – 43 , 47 ]. While most countries contributed with a single study to this review, two studies provided data for immigrants coming from Vietnam, Philippines, Cambodia, Lao PDR and Myanmar [ 18 , 21 ], no publications were found from Timor-Leste and Brunei. Twenty-two cross-sectional studies reported seroprevalence data while 13 publications reported only incidence data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 35 included publications, the largest number were for Thailand (n = 20) [ 23 38 , 44 – 46 , 51 ] followed by Malaysia (n = 5) [ 20 , 41 – 43 , 47 ]. While most countries contributed with a single study to this review, two studies provided data for immigrants coming from Vietnam, Philippines, Cambodia, Lao PDR and Myanmar [ 18 , 21 ], no publications were found from Timor-Leste and Brunei. Twenty-two cross-sectional studies reported seroprevalence data while 13 publications reported only incidence data.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, a survey from Vietnam [ 39 ], conducted in 1994, showed an almost complete seroconversion by 10 years of age. Twenty years later, a survey conducted between 2011 and 2017 among immigrant women in Korea [ 21 ] from countries including Cambodia (n = 58), the Philippines (n = 85) and Vietnam (n = 422), suggested an HAV endemicity age shift pattern in Vietnam (60% by 20–29 years of age and 80% by 30–40 years of age) and the Philippines (78% by 20–29 years of age and 72% by 30–40 years of age), but not in Cambodia (100% HAV seropositivity by 20–29 years of age).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 1981 study that recruited 564 Vietnamese refugees, 90% were positive for anti-HAV at 15 years old [ 105 ]. However, in a recent study that looked at 422 adult female immigrants from Vietnam, only 59% were seropositive [ 106 ]. Genotypic characterization of the virus showed that genotype 1A is the most common among pediatric patients diagnosed with hepatitis A [ 107 ].…”
Section: Epidemiology and Seroepidemiology Of Hepatitis A In The Who Wprmentioning
confidence: 99%
“…Refs. [ 10 , 11 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Table A1unclassified